ANALISA DAMPAK RASIO KEUANGAN PERBANKAN TERHADAP PROFITABILITAS BANK BERDASARKAN MODAL INTI (KBMI) PADA KELOMPOK BANK DI INDONESIA - Subrini; Masyhuri Hamidi; Fajri Adrianto (Halu Oleo University, 2024)
This research aims to investigate the analysis of the relationship between banking financial ratios and profitability using the purposive sampling technique in the form of panel data. The research sample was derived from 47 banking sectors listed on the BEI stock exchange from 2013 to 2022, with a total of 470 firm-year observations. The regression method employed was the Ordinary Least Squares (OLS) data panel, and it underwent tests for regression model selection, classical assumptions, robustness, and the Generalized Least Squares (GLS) method. The research findings indicate that CASA is a determining factor for banks in general to enhance Return on Assets (ROA), especially in the small bank group (KBMI 1 and 2). BOPO has been a hindering factor for banks in general to achieve profitability (ROA and ROE) over the past 10 years. In the pre and POST economic crisis of Covid-19, the Loan to Deposit Ratio (LDR) is a hindering factor for banks in general to achieving profitability. Interestingly, as long as the economic crisis, the opposite is true, LDR became a determining factor in increasing profitability, especially in the large bank group (KBMI 3 and 4).